From gesture to adverbial – Swedish det as an example of linguistic polysemy - Data-Bukowska, Ewa (Folia Scandinavica Posnaniensia, 2009)
Every grammar of the Swedish language provides information concerning the unit det. The Swedish det can be used both pronominally and adnominally, fulfilling a wide range of functions in the language. However, in traditional grammar one does not pay attention to the links and mutual relations between the individual occurrences of this unit. Thus, within such a framework, the Swedish det can be treated as an extreme example of homonymy. Is that possible in language? The main goal of this article is to show the semantic value of the unit det (in its nominal function) in contemporary Swedish, adopting the perspective of Cognitive Grammar. I shall try to prove that all uses of this unit are linked to each other semantically. Thus, the meaning ascribed to det constitutes a complex network of senses rooted in the prototype, which is a cognitive reference point within the category. The article can be interpreted in a wider context of the research concerning the use of units which are functionally “related” to the Swedish det in various languages, e.g. the English it, the German es, the Polish to etc.